Eksplorasi Faktor yang Mempengaruhi Loyalitas Konsumen Ojek Online - Mohammad Rizal Gaffar; Mamun Sutisna (Jurnal Sekretaris dan Administrasi Bisnis, 2020)
Ojek Online is a motorbike based public transportation application. Gojek and Grab is the top ojek online in Indonesia. There are still many local startups in the ojek online business such as Ladyjek, Blu-jek, and Motorcycle taxi. They are unable to compete because their rates are less competitive. This is because the capital owned is not too big to do the "burning money" like other startups. A model is needed to analyze what factors affect passenger using ojek online services. So, we hope local startups can compete with their innovation based on needs from consumer which will be analyzed in this research. There have been several studies that have examined the behavior of users of public transportation services, both of conventional and online transportation, which is currently booming. However, the author has not found a detailed study observing what factors influence the behavior of ojek online’s users. Therefore, the authors develop a model that integrates variables which include overall service indicators not only the application but also overall aspects like the driver and usefulness of the services. In this study a set of questionnaire was distributed and used to measure the model and data taken as many as 200 samples. Partial Least Square is used to analyze the data that has been taken. The measurement results show the model has a predictive power that is good enough to measure customer loyalty from ojek online user and all hypotheses are accepted.